Oil palm intercropping in Uganda – an assessment of farmer practices and suggestion of alternatives - Namanji, S.; Ssekyewa, C.; Slingerland, Maja (2020)
The expansion of oil palm in Uganda has undoubtedly brought economic benefits including jobs and import substitution among others, but these have been accompanied by negative social and environmental impacts. This brief is the latest in a series that has investigated these impacts, but is the first to propose new models of intercropping for Uganda. International experience shows that growing food or cash crops with oil palm in agroforestry systems can increase smallholder incomes, resilience and biodiversity and surveys show that farmers in Uganda are already experimenting and are ready to adopt intercropping on a wider scale.